2021
DOI: 10.3389/fvets.2021.621699
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Trypanosomiasis in Wildlife—Implications for Humans at the Wildlife Interface in Africa

Abstract: While both human and animal trypanosomiasis continue to present as major human and animal public health constraints globally, detailed analyses of trypanosome wildlife reservoir hosts remain sparse. African animal trypanosomiasis (AAT) affects both livestock and wildlife carrying a significant risk of spillover and cross-transmission of species and strains between populations. Increased human activity together with pressure on land resources is increasing wildlife–livestock–human infections. Increasing proximi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 147 publications
(195 reference statements)
0
50
0
Order By: Relevance
“…In humans, the disease is generally categorized based on the protozoan species, i.e., Chagas disease (American trypanosomiasis) and sleeping sickness (human African trypanosomiasis). Both forms of the disease are prevalent in low-income countries of America, Africa, and Asia and it is of major concern since it affects wildlife ( 2 ) and livestock such as equines (horses and camels), and large and small ruminants (i.e., bovines, ovines, and caprines) ( 3 ). This affects livestock productivity especially among horses, donkeys, camels, sheep, goats, and buffalo due to its associated economic burden ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…In humans, the disease is generally categorized based on the protozoan species, i.e., Chagas disease (American trypanosomiasis) and sleeping sickness (human African trypanosomiasis). Both forms of the disease are prevalent in low-income countries of America, Africa, and Asia and it is of major concern since it affects wildlife ( 2 ) and livestock such as equines (horses and camels), and large and small ruminants (i.e., bovines, ovines, and caprines) ( 3 ). This affects livestock productivity especially among horses, donkeys, camels, sheep, goats, and buffalo due to its associated economic burden ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…Similar to previous reports from Lambwe, the second-highest infections were of T. vivax (31.2%, 83/266) and after that, T. brucei brucei (27.4%, 73/266) ( 7 , 13 ). The role of cattle and wildlife in sustaining the sylvatic cycle of T. brucei rhodesiense , especially in wildlife–livestock interfaces, is well-established ( 6 , 11 , 38 40 ). In a survey on small ruminants and cattle in Ngorongoro conservation in Tanzania, Ruiz et al ( 39 ) reported that 2.1% of cattle had T. brucei rhodesiense .…”
Section: Discussionmentioning
confidence: 99%
“…The lack of explicit information for the prevalence of pathogens, especially in the wildlife-livestock-human interfaces, is a major drawback for effective control of AAT ( 11 ). Consequently, the recently defined progressive control pathway for AAT advocates for enhanced research to understand the risks of trypanosomosis to guide the selection of priority intervention areas as the first step toward effective control ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…With respect to trypanosomes, the potential for infection with multiple species is particularly high because these parasites have an unusually broad host range, allowing frequent interactions between species in diverse hosts. Reflecting this, a large number of studies in different regions have reported the co-circulation of T. brucei , T. congolense and T. vivax , and these have been detected both in surveyed livestock and game animals [ 10 ], as well as in trapped tsetse flies (e.g. [ 11 , 12 ]).…”
Section: Epidemiology Of Co-infectionmentioning
confidence: 99%